Investigating the New Zealand policy response to residential methamphetamine contamination : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Public Health, SHORE & Whāriki Research Centre, College of Health, Massey University, New Zealand. EMBARGOED until further notice. - Sanchez Lozano, Claudia Denisse (Massey University, 2023)
Introduction: Methamphetamine use and manufacture has been an on-going issue in New Zealand since the early 2000s. Clandestine manufacture of methamphetamine is associated with hazardous chemicals that contaminate the area in which this activity occurs, with potential health harms to occupants of these structures. From 2010, a set of policies addressing methamphetamine contamination of housing were implemented in the residential sector to determine whether a property is contaminated and the appropriate response. In 2018, a scientific review prompted a dramatic change in the recommended contamination thresholds and related policies, particularly those of Housing New Zealand. This PhD thesis aims to investigate and critically evaluate the policy process and change in approach to residential methamphetamine contamination in New Zealand. Methods: This research applied a qualitative approach to case study research. The methods used included analysis of local and overseas literature, official reports, guidelines, and policy documents, analysis of legal decisions, comparative case study analysis, and qualitative interviews of stakeholders and key experts. More specifically, thematic and content analyses of legal decisions addressing methamphetamine contamination in housing before (N = 685) and after the change in approach (N = 195) were completed. A comparative analysis of the policy responses and outcomes for public housing authorities in the United States and New Zealand was also conducted. In addition, a thematic analysis was carried out on the transcripts from semi-structured interviews with 13 New Zealand key informants (KI) from government, industry, the residential and academic sectors. Results: A range of unintended consequences from residential methamphetamine contamination policies were observed, including termination of tenancies and substantial financial expenditure on testing and remediation. Tenants were particularly disadvantaged by the policies, with public housing tenants facing additional consequences including their suspension from the public housing list. Stakeholders highlighted the need for additional guidance and industry regulation. Inconsistencies in the adoption and interpretation of policies were observed across the residential sector, particularly in the analysis of Tenancy Tribunal decisions. The US public housing authority shared many similarities in policy response and outcomes to Housing New Zealand, starting with a zero-tolerance to eventually moving to a harm reduction approach. Conclusions: Limited scientific evidence of the health risks from methamphetamine contamination in houses enhanced the influence of the political context and fundamental attitudes to drug use in the development and implementation of these policies in New Zealand. Additional guidance is required and it should balance scientific uncertainties with the outcomes of policy implementation. Evaluation of future interventions is needed to avoid further unintended consequences.
Permission for the publication of Chapters 6, 7 ,8 & 9 was obtained, and for the re-use of Figures 3 & 4.
Thesis embargoed until further notice.
Keywords: Methamphetamine; Chemical laboratories; Environmental aspects; Housing and health; Government policy; New Zealand; 440706 Health policy